Virtues and defects of peruvians colonial heritage - León, Ramón (2010)
This communication reports a study in 691 students (414 women, 277 men, 16-60 years old), who were asked to rate (on a scale of 0 to 4) ten virtues and ten defects of an average Peruvian. The virtues considered were hard-working, honest, enterprising, ambitious, thrifty, sympathetic, creative, tidy, proud, and wel.organized; the defects were lazy, corrupt, conformist, fatalist, spendthrift, individualist, passive, envious, inhibited, talkative. They were asked too to rate the influence of colonial Spanish heritage on these virtues and defects (0 to 4). The average Peruvians were seen as creative and har.working, but in reference to the defects as corrupt, inhibited and envious. The influence of colonial Spanish heritage on the virtues was evaluated as not so high, but it was perceived as high in reference to defects.